Do graded representations support abstract thought?. (February 2021) - Carstensen, Alexandra; Frank, Michael C
Abstract : Relational reasoning requires the reasoner to go beyond her/his specific experience, abstracting from items to make inferences about categories and kinds on the basis of structural or analogical similarities. Reasoning about the relations same and different is one of the best-studied cases of relational reasoning, both across species and over human development, and has become a paradigm case study for abstract representation. However, decades of careful study have nonetheless produced seemingly contradictory findings — with surprising successes and puzzling failures — in both the comparative and developmental literatures. In this article, we review these literatures and suggest first steps toward a reconciliation of these contradictions by suggesting that same-different reasoning is supported by graded representations.